Terrestrial glacial geomorphology of surge-type and non-surge-type glaciers on Svalbard ... - McCerery, Rebecca; Davies, Bethan Joan; Lovell, Harold; Pearce, David Anthony; Calvo-Ryan, Rosalia; Małecki, Jakub; Woodward, John (Taylor & Francis, 2024)
This paper presents a map of terrestrial glacial geomorphology of eleven surge-type and non-surge-type glacier forefields in southwest and west Spitsbergen, Svalbard. Glacier forefields were mapped using a combination of field surveys and the use of an uncrewed airborne vehicle in September 2022 and satellite imagery captured in 2020, with mapping performed in ArcGIS Pro at a 1:5000 scale. Maps were constructed for glaciers in Van Kuelenfjorden and Van Mijenfjorden (southwest Spitsbergen), and in Isfjorden, Billefjorden a fjord branch of Isfjorden and St. Jonsfjorden (west Spitsbergen), to obtain a breadth of glacier types and features representative of glacial landsystems on Svalbard. The detailed landform inventory was divided into: (i) ice marginal, (ii) subglacial, (iii) glaciofluvial and glaciolacustrine, (iv) supraglacial and (v) other non-glacial and contemporary features. These detailed maps provide a geomorphological insight into the past and present characteristics of glaciers on Svalbard. ...